The Cultural Adaptation of Step-by-Step: An Intervention to Address Depression Among Chinese Young Adults - Sit, Hao Fong; Ling, Rui; Lam, Agnes Iok Fong; Chen, Wen; Latkin, Carl A.; Hall, Brian J. (Frontiers in Psychiatry, 2020)
Background Digital mental health interventions leverage digital communication technology to address the mental health needs of populations. Culturally adapting interventions can lead to a successful, scalable mental health intervention implementation, and cultural adaptation of digital mental health interventions is a critical component to implementing interventions at scale within contexts where mental health services are not well supported. Objective The study aims to describe the cultural adaptation of a digital mental health intervention Step-by-Step in order to address depression among Chinese young adults. Methods Cultural adaptation was carried out in four phases following Ecological Validity Model: (1) stage setting and expert consultation; (2) preliminary content adaptation; (3) iterative content adaptation with community members; (4) finalized adaptation with community feedback meetings. Cognitive interviewing was applied to probe for relevance, acceptability, comprehensibility, and completeness of illustrations and text. Six mental health experts and 34 Chinese young adults were recruited for key informant interviews and focus group discussions. Results We adapted the text and illustrations to fit the culture among Chinese young adults. Eight elements of the intervention were chosen as the targets of cultural adaptation (e.g., language, metaphors, content). Samples of major adaptations included: adding scenarios related to university life (relevance), changing leading characters from a physician to a peer and a cartoon (acceptability), incorporating two language versions (traditional Chinese and simplified Chinese) in the intervention (comprehensibility), and maintaining fundamental therapeutic components (completeness). Conclusion This study showed the utility of using Ecological Validity Model and a four-point procedure framework for cultural adaptation and achieved a culturally appropriate version of the Step-by-Step program for Chinese young adults.